2012
DOI: 10.7314/apjcp.2012.13.4.1579
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Prognostic Analysis of Serum Protein Expression in Esophageal Squamous Cell Cancer

Abstract: Objective: To assess differences in serum proteins in esophageal squamous cell carcinoma patients. Methods: 144 esophageal squamous cell carcinoma patients and 50 healthy volunteers were included in this study, with surface-enhanced laser desorption-ionization time-of-flight mass spectrometry and weak cation exchange magnetic beads. Follow-up allowed the relations between serum proteins and prognosis to be analyzed. Results: A total of 93 protein peaks were detected (molecular weight range: 1500-30000), 10 dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In search of ESCC prognostic serum biomarkers using SELDI-TOF MS, Jiang et al found no difference between protein profiles patients with more than 2-year and less than 2-year survival [58]. Furthermore, only 1 protein peak differed significantly between stage III disease patients stratified by this survival criterion.…”
Section: Esccmentioning
confidence: 95%
See 1 more Smart Citation
“…In search of ESCC prognostic serum biomarkers using SELDI-TOF MS, Jiang et al found no difference between protein profiles patients with more than 2-year and less than 2-year survival [58]. Furthermore, only 1 protein peak differed significantly between stage III disease patients stratified by this survival criterion.…”
Section: Esccmentioning
confidence: 95%
“…By conducting subgroup analysis based on the state of lymph node metastasis, a significant clinicopathological prognostic factor, Uemura et al succeeded in discovering a reliable prognostic biomarker [23]. Similarly, Jiang et al identified a prognostic biomarker by correlation with EC clinical stage [58]. Patients' stratification according to clinical background would allow compensation for the heterogeneity of molecular mechanisms involved in EC and provide a potential to increase the sensitivity and specificity of EC prognostic biomarkers.…”
Section: Perspectives Of Prognostic Biomarkersmentioning
confidence: 97%